INSIGHTS ON CAREGIVING IN THE VILLAGES, FL: FINDINGS FROM CAREGIVERS PARTICIPATING IN A BRAIN HEALTH CLINICAL TRIAL. (11th November 2018) - Roberts, M; VandeWeerd, C; Roth, D; Sappington, E; Alluri, S; Yalcin, A; Lowenkron, J
Abstract: While recent studies indicate that conditions for caregivers may be improving, those providing care for persons with dementia and those experiencing high role strain are still at risk for adverse health outcomes. To better understand the factors that impact caregiver's health, this study assesses domains such as role strain, depression, and memory in relation to caregiving demand. Findings are presented from an on-going clinical trial evaluating a novel electroencephalography (EEG) technology to assess brain health conducted between 8/30/2017-2/1/2018 in The Villages-an active-senior-lifestyle community in Central Florida. Health assessment data is available for 889 participants, including 77(9%) self-reported informal caregivers. Caregivers were predominantly female (F=56, M=21). 45% provided care to recipients with Alzheimer's or dementia (N=35). On average, caregivers reported providing 19.2 hours of care each week (SD=34.7) and 6.7 years caregiving (SD=10.3). Providing care for recipients with dementia was not significantly related to level of strain χ 2(2, N=77)= 5.30, p=.07. Caregivers demonstrated better recall than non-caregivers as measured by word list memory task delayed recall scores (t[887]= 2.36, p = .018). Being a caregiver was associated with increased levels of sadness (U=30, 177 z=-2.07, p=.039) and increased feelings of hopelessness for the future, as measured by Beck's-Depression-Inventory (U=29, 574 z=-2.28, p=.023). High levels of role strain were not associated with increased levels of depression, but were positively associated with hours of care provided weekly (U= 418, z=-2.21 p=.003). High levels of social support and services within the community may offset adverse health outcomes. Implications for policy and practice are discussed.